Cervical intraepithelial neoplasia: pathogenesis and diagnosis (a literature review) - N A Sheshukova; I O Makarov; E A Chulkova; R R Averchenko; O V Chulkova (IP Berlin A.V., 2014)
This article reflects the current views on the etiology and pathogenesis of cervical intraepithelial neoplasia, as well as the fundamental questions concerning the diagnosis of pathological processes of the cervix, that are covered in detail.